Diseño a nivel de laboratorio de un espaciador con base en Una resina polimérica para el control de gas en los procesos de cementación para la sección del liner de 7” en el campo Chuira (2017)
In this text several spacers are designed and based on a polymeric resin, in oder to know the best design that could be implemented on gas migration control during the cement process of Chuira Field, based on laboratory tests on distinct designs obtained on the Chuira field characteristics Chuira field.